Factors Explaining Corporate Social Responsibility Expenditure in India. (April 2015) - Rai, Shachi; Bansal, Sangeeta
The passage of the CSR clause in the Companies Act, 2013 has been a landmark decision. This article tries to understand the reasons that determine the CSR expenditure by firms before the implementation of the law through a cross section study. The study finds that industry types and environmental factors determine the CSR expenditure by firms and also explains the endogenous relationship between CSR expenditure and profitability which had remained unexplored for Indian firms.